Management of Oral Lesions in Paraquat Poisoning - A Case Report - C., Muralee Mohan; Shetty, Pratiksha; Gohil, Saurabh M.; Sharma, Jitesh; Roy, Satadru (Journal of Health and Allied Sciences NU, 2017)
Paraquat is a herbicide with a good occupational safety record, but a high mortality after intentional ingestion that has proved refractory to treatment. For nearly three decades p concentration–time data have been used to predict the outcome following ingestion, however, none of the published methods has been independently or prospectively validated. However, poisoning is an uncommon entity in India. We report a case of oral lesions associated with poisoning and management of the mucosal burns associated with it along with medical management of poisoning in general.
Keywords: paraquat; poisoning; choline salicylate; benzalkonium chloride